Outcomes and prognostic factors for major salivary gland carcinoma following postoperative radiotherapy. (March 2016) - Hosni, Ali; Huang, Shao Hui; Goldstein, David; Xu, Wei; Chan, Biu; Hansen, Aaron; Weinreb, Ilan; Bratman, Scott V.; Cho, John; Giuliani, Meredith; Hope, Andrew; Kim, John; et al.
Highlights: PORT with 3D-CRT/IMRT for salivary gland carcinoma achieved excellent outcomes. DM was the most frequent cause of treatment failure and cancer-related mortality. Prognostic factors were stage III–IVB, LVI, R1 and high risk pathology. Further research is required to determine the incremental benefit of chemotherapy. Summary: Purpose: To report outcomes of postoperative radiotherapy (PORT) for major salivary gland carcinoma (SGC) and identify patients at high risk of distant metastases (DM). Methods and materials: Patients with major SGC treated between 2000–2012 were identified. All patients underwent initial primary resection, with neck dissection (ND) therapeutically (if N+) or electively in high risk N0 patients. PORT was delivered using 3D-CRT or IMRT. Multivariable analysis (MVA) assessed predictors for DM, cause-specific (CSS) and overall survival. Results: Overall 304 patients were identified: 48% stage III–IVB, 22% lymphovascular invasion (LVI), 50% involved margins and 64% high risk pathology. ND was performed in 154 patients (51%). Adjuvant chemotherapy was used in 10 patients (3%). IMRT was delivered in 171 patients (56%) and 3D-CRT in 133 (44%). With a median follow-up of 82 months, the 5-(10-) year local, regional, distant control, CSS and OS were 96% (96%), 95% (94%), 80% (77%), 83% (82%) and 78% (75%), respectively. DM was the most frequent treatment failure ( n  = 62). On MVA, stage III–IVB and LVI significantly correlated with DM, CSS and OS, while positive margins predicted DM and CSS, and high risk pathology predicted DM. No grade ⩾4 RTOG late toxicity was reported; 9 patients had grade 3, including osteoradionecrosis ( n  = 4), neck fibrosis ( n  = 3), trismus ( n  = 1) and dysphagia ( n  = 1). Conclusions: Surgery and PORT with 3D-CRT/IMRT produced excellent long-term outcomes. Further research is required for patients with stage III–IVB, LVI, positive margins and high risk pathology to determine the incremental benefit of systemic therapy in management of SGC.